1998
DOI: 10.1007/s002040050522
|View full text |Cite
|
Sign up to set email alerts
|

The role of glutathione S-transferase- and cytochrome P450-dependent metabolism in the olfactory toxicity of methyl iodide in the rat

Abstract: The aim of this study was to investigate the role of metabolic activation in the olfactory toxicity of methyl iodide (MeI). Adult male rats were exposed via nose-only inhalation to 100 ppm MeI for 0-6 h, and non-protein sulphydryl (NP-SH) concentrations determined in selected tissues. Depletion of NP-SH occurred in all tissues, but was most marked and rapid in the respiratory epithelium of the nasal cavity and the kidney. Olfactory, lung and liver NP-SH levels were affected to a lesser extent, and those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…The reason for the increased susceptibility to methimazole in GSH-depleted mice is not known and no further attempts to examine these effects have been made. An increased susceptibility has also been observed following administration of the olfactory toxicant methyl iodide to GSH-depleted animals (8).…”
Section: Discussionmentioning
confidence: 98%
“…The reason for the increased susceptibility to methimazole in GSH-depleted mice is not known and no further attempts to examine these effects have been made. An increased susceptibility has also been observed following administration of the olfactory toxicant methyl iodide to GSH-depleted animals (8).…”
Section: Discussionmentioning
confidence: 98%
“…p-Chloromercuribenzoic acid (PCMB), an anionic probe of moderate size, caused the oocytes to swell and burst at a concentration of 0.2 mM (data not shown). This was attributed to the entry of PCMB into the oocytes by non-ionic diffusion and the subsequent inhibition of energy metabolism, since several steps in glycolysis and oxidative phosphorylation are known to be sensitive to sulphydryl reagents [25][26][27]. By contrast, p-chloromercuribenzosulfonate (PCMBS), a bulky anion believed to be membrane impermeant [14,28], did not cause the oocytes to burst and had little or no effect on wild-type CFTR-mediated Cl -currents, even at concentrations as high as 1.3 mM.…”
Section: +mentioning
confidence: 99%
“…Inhalation of methyl iodide (MeI) results in toxicity to many organs including the olfactory epithelium (30), where it undergoes conjugation with glutathione catalysed by glutathione S-transferase T1-1 (6). Although this appears to be a detoxification reaction (7), it has been suggested that the resultant rapid and extensive depletion of intracellular glutathione may make the olfactory epithelium vulnerable to oxidative damage (7). Methyl methacrylate (MMA) is a potent olfactory toxin following inhalation exposure (14,15).…”
Section: Introductionmentioning
confidence: 99%